TID Radiation Effects in Si STP6N65M2 and SiC SCT2H12NZGC11 Power MOSFET - Ganapathy, Thannirmalai (IRC, 2019)

(untitled)
This paper discusses the total ionizing effects on Silicon Power MOSFET and Silicon Carbide Power MOSFET. It is common that an electronic device in space to face high dose of radiation. Power MOSFET is also a part of the electronic system used in outer space to power up devices. The performance of a Power MOSFET will be affected when in contact with space radiation. The main aim is to understand the problems faced by the current Power MOSFET due to radiation. The working principle of a Power MOSFET have been understand and the behavioral comparison have been made on Silicon and Silicon Carbide Power MOSFETs. Single Event Effect (SEE), Total Ionizing Dose (TID), and Displacement Damage (DD) have been identified as the three types space radiation that effect semiconductors. When in contact with radiation the Power MOSFET experiences electrical and physical changes. The leakage, power consumption, threshold voltage, on state resistance, break down voltage will change, and shift based on the radiation. Silicon STP6N65M2 Power MOSFET and Silicon Carbide SCT2H12NZGC11 Power MOSFET are used for the irradiation process. Both the Silicon and Silicon Carbide Power MOSFETs are compared and tested before and after the irradiations. The threshold voltage, current-voltage (I-V) characteristics and capacitance-voltage (C-V) characteristics is determined from the testing data and calculations. The cobalt-60 gamma ray is used to the Total Ionizing Dose. Both the Power MOSFETs are irradiate at different dose level of 100k rad, 300k rad, 600k rad, 1M rad and 1.5M rad. Three samples from Silicon and Silicon Carbide Power MOSFET were tested at each dose level. The Power MOSFET’s performance were determined and categorized by plotting the static and dynamic characteristic. Both Power MOSFET were affected by the cobalt-60 gamma ray as the total amount dose is increased. The Silicon Carbide Power MOSFET has better withstand to the Total Ionizing Dose radiation compared to Silicon Power MOSFET. It is vital to make sure the Power MOSFET does not affected by the radiation at the outer space.